Penerapan Awal Pengenalan Teknologi Informasi Deteksi Penyakit Hama Tanaman Vanila pada Karang Taruna Lima Sulapa - Lilis Nur Hayati; Asdar Djamereng; Sitti Rahbiah; Rayhana Bahar; Mush'ab Al Mubarak; Putri Bimadayanti; Fitra Ramadani (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
EARLY APPLİCATİON OF INFORMATİON TECHNOLOGY INTRODUCTİON OF DİSEASE AND PEST DETECTİON OF VANİLLA PLANTS TO YOUTH KARANG KARUNA LİMA SULAPA GATTARENG İN BULUKUMBA REGENCY. Agriculture is one of the main pillars of the country's economy, contributing significantly to Gross Domestic Product (GDP) and employment. The purpose of the service is to introduce information technology in the detection of diseases and pests of vanilla plants to youth Karang Taruna Lima Sulapa Gattareng in Bulukumba Regency. The problem faced is the lack of knowledge and ability of partners in detecting diseases and pests of vanilla plants. This activity was carried out through three stages, namely preparation, implementation, and evaluation. The socialization was attended by 38 participants who followed the program from start to finish. The results of the socialization activities showed a significant increase in understanding from the pre-test results showed 45.36%, while the post-test results increased to 82.79%. In conclusion, the service program succeeded in increasing partners' knowledge and awareness of the importance of information technology in detecting diseases and pests in vanilla plants.